Communication Patterns Government Prevents Spread of COVID-19 Hoax News on Social Media - Annisa Weriframayeni; Novia Amirah Azmi; Aqil Teguh Fathani (Universitas Musamus, Merauke, Papua, 2022)
he spread of fake news on social media with the theme of COVID-19 is on the rise and knows no bounds. Various title taglines, contents, and narrations about COVID-19, Masks, and Vaccine are rapidly influencing individuals to be frightened to participate in activities. The goal of this research is to expand on the evaluation of long-term intelligent communication patterns in order to predict the propagation of COVID-19 false news on social media. This study was conducted primarily to investigate the factors influencing public opinion regarding the spread of COVID-19, victim cases, immunizations, and origins, as well as the government's response in West Sumatra Province. Data were gathered through in-depth interviews and direct observation, as well as in-depth interviews with six different sources and the distribution of 120 questionnaires. 112 questionnaires (93.3%) were collected and analyzed using the Structural Equation Modeling Partial Least Squares (SEM) technique in SmartPLS 3.0. The findings revealed a significant relationship between public opinion and the government's response to COVID-19 pandemic issues on social media. The findings indicate that a robust response to socialization, education, and public monitoring is required for the correct and intelligent use of social media. Digital literacy and information filtering must be enhanced, and perpetrators of disseminating COVID-19 false information must face strong and concrete penalties. Strict penalties and structured appeals will gradually have an impact on the media, which is not in charge of conveying COVID-19 information to the public